Pengaruh Kegiatan Dakwah Muslim Qur’anic Academy Terhadap Religiusitas Peserta - Nabila, Alifia; Sumijaty, Siti; Nur Chidayah, Prita Priantini (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research aims to find out how much influence da'wah activities at the Muslim Qur'anic Academy have on the participants' religiosity. The theory used is Stimulus-Organism-Response (S-O-R) proposed by Hovland. This research uses quantitative methods. The results of data processing show a coefficient of determination of 59.4%. Hypothesis testing showed a significance value of 0.000 (<0.05), indicating a significant influence of da'wah activities on participants' religiosity. The conclusion is that da'wah activities have an insufficient influence on participants' religiosity because they are influenced by the participants' Islamic educational background and their involvement in other hijra communities. Even though the material presented was good, some of it was considered lacking in depth.